Seasonal dynamics of nutrients concentration and dissolved oxygen content in the rivers of southern Primorye - Anna S. Vazhova (Известия ТИНРО)
Rivers are the main source of terrigenous nutrients to the coastal sea which could be responsible for such adverse impacts as red tides or hypoxia in the estuarine areas. To evaluate the rivers influence on chemical environments in the coastal zone, monitoring of water properties in the rivers of southern Primorye was conducted in 2016 (and continues till nowadays). Retrospective data of chemical measurements on the Razdolnaya, Artemovka, Knevichanka and Ryazanovka rivers in different seasons of 1985 were used for comparison with modern data. Prominent seasonal dynamics of chemical parameters is revealed that generally corresponds to seasonal changes of freshwater discharge caused by monsoon cycle of precipitations. The seasonal dynamics of water temperature is conditioned by climate features of the region and geographic location of the rivers: the temperature at the surface is about 0оC in February, then rises in spring-summer and decreases in autumn, with the maximum values in August as 26-27оС for the flat rivers and 18-20оС for the mountain rivers. The pH variations are conditioned by the carbon dioxide saturation in water, so its level is 6.1-7.2 in winter and 7.4-8.2 in summer. Nutrients, except iron, have the maximum concentration in winter (DIN ~2.5 µM/L, DIP ~0.5 µM/L, silicates ~115.0 µM/L) but the iron concentration is the highest in spring (~0.1 mg/L). However, natural seasonal variation of nutrients is distorted by anthropogenic load for some rivers with industrial and agricultural activity in the basins, including the territories of P.R. China (Suifen/Razdolnaya River): their waters are the richest by nitrogen and phosphorus in summer (DIN ~45.0 µM/L, DIP ~0.5 µM/L) and by dissolved iron in autumn-winter (~0.9-1.3 mg/L). Spatial variability is very similar between all nutrients in any season (correlation coefficients between DIN and Fe concentrations are 0.75-0.99, between DIP and Fe - 0.83-0.99) that means that their growth in the polluted rivers has common nature, presumably a decomposition of organic wastes Being transferred. Transferred to the sea, the nutrient elements of terrestrial origin are converted back to organic matter enhancing the coastal waters productivity, but consequences of this impact are principally different for the natural regime with the winter-spring maximum and for the distorted regime with the summer-fall maximum. Huge oxygen demand determines the lowered DO in the Suyfen/Razdolnaya and Knevichanka in winter. Other rivers of southern Primorye (Ryazanovka, Barabashevka, Kievka, Partizanskaya, Sokolovka, Artemovka) could be considered as «clean» ones, following to Russian standards of water quality. Seasonal variability of oxygen content in their waters is driven by changes of water temperature and photosynthesis. Comparison of the long-term changes in water quality for the rivers Razdolnaya, Artemovka, Knevichanka and Ryazanovka over the last 30 years (relative to 1985) has revealed unfavorable changes of dissolved oxygen content for the Razdolnaya and Knevichanka, whereas the changes are not significant for the Artemovka and the oxygen content has increased for the Ryazanovka. The latter indicates the Ryazanovka water quality improvement that is important since a fish farm is located on the river.